IMPROVEMENT OF WORK SAFETY AND HEALTH IN IMPROVING THE QUALITY OF PRODUCTION PROCESS USING THE HAZARD AND OPERABILITY STUDY METHOD - Nugraha, Evan (2019)
Occupational safety and health is an important part of a company, especially in industrial companies. PT Dirgantara Indonesia is a company that manufactures aircraft in the CN hangar and Helicopter in the MK hangar. Every production process must pay attention to the Occupational safety and health applied, this will affect the quality of the product to be produced. The company applies work safety standards, but in its implementation there are still some potential that can cause work accidents. If the potential for work accidents that arise can be identified, then the number of occupational accidents can decrease. The first stage is to identify the source of hazards in the work area, then analyze the risk of occupational hazard sources using the Hazard and Operability Study method. The results of the survey in the lower production process found 8 sources of danger, namely mosukuleskeletal disorders, hearing, vision health, injuries to the hands, injuries to the head, installation on the floor, jig bumps and poor lighting. The results of this study are proposed improvements with a number of recommendations for Occupational safety and health support facilities. The purpose of the proposal is to improve production quality and reduce potential health.